2021
DOI: 10.3390/foods10061169
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of FAD2-1 Gene Expression Alters Lysophospholipid Composition in the Endosperm of Rice Grain and Influences Starch Properties

Abstract: Small quantities of lipids accumulate in the white rice grains. These are grouped into non-starch lipid and starch lipid fractions that affect starch properties through association with starch. Lysophosphatidylcholine (LPC) and lysophosphatidylethanolamine (LPE) are two major lipid classes in the two fractions. Using high-oleic rice grains, we investigated the fatty-acid composition in flour and starch by LC-MS and evaluated its impact on starch properties. In the wild-type grain, nearly 50% of fatty acids in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…However, the eating quality of brown rice is usually not desirable and needs to be improved. Although fatty acids are minor components of the rice endosperm, they may play an important role in starch quality [ 27 , 28 , 29 ]. However, the effect of unsaturated fatty acids on the eating quality of rice is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, the eating quality of brown rice is usually not desirable and needs to be improved. Although fatty acids are minor components of the rice endosperm, they may play an important role in starch quality [ 27 , 28 , 29 ]. However, the effect of unsaturated fatty acids on the eating quality of rice is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that downregulation of the major FAD2-1 resulted in increased oleic acid and reduced linoleic and palmitic acids in rice grains ( Zaplin et al., 2013 ). Luo et al. (2021a , 2021b) found that knockdown of FAD2-1 also influenced starch properties ( Luo et al., 2021a ).…”
Section: Genetic Basis Of Rice Ecq Improvementmentioning
confidence: 99%
“… Luo et al. (2021a , 2021b) found that knockdown of FAD2-1 also influenced starch properties ( Luo et al., 2021a ). Khan et al.…”
Section: Genetic Basis Of Rice Ecq Improvementmentioning
confidence: 99%
“…These complexes are formed during the synthesis of starch. They are best known for forming complexes with amylose molecules stabilized by hydrogen bounds [43,66], which inhibit the swelling of rice and reduce susceptibility to starch digestive enzymes. The study by Ye et al (2018) shows that the presence of endogenous lipids has effects on rice flour digestibility.…”
Section: Lipidsmentioning
confidence: 99%
“…Triacylglycerols are the major non-starch lipids present in the rice grain; free fatty acid and lysophospholipids are the major starch lipids in the rice grain [ 43 ]. Starch lipids, although they exist in a smaller proportion, still play an important role in starch functionality and quality, affecting its digestibility by modifying starch swelling, gelatinization, and pasting [ 66 ]. These complexes are formed during the synthesis of starch.…”
Section: Rice Macronutrientsmentioning
confidence: 99%